Unexpected Genetic Cause in Two Female Siblings with High Myopia and Reduced Visual Acuity - Preising, M. N.; Friedburg, C.; Bowl, W.; Lorenz, B.; Justus Liebig University Giessen (My University, 2018)
In daily life, myopia is a frequent cause of reduced visual acuity (VA) due to missing or incomplete optical correction. While the genetic cause of high myopia itself is not well understood, a significant number of cases are secondary to hereditary malfunctions or degenerations of the retina. The mechanism by which this occurs remains yet unclear. Two female siblings, 4 y and 2 y, respectively, from a consanguineous Pakistani family were referred to our department for reduced VA and strabismus. Both girls were highly myopic and hence were further examined using standard clinical tests and electroretinography (ERG). The latter confirmed confounded electrical coupling of photoreceptors and bipolar cells. Further inquiry and testing confirmed a similar condition for the father including impaired night vision, reduced VA, photophobia, and an equally characteristic ERG. Findings in the mother were unremarkable. Subsequent genetic analysis of autosomal recessive and X-linked genes for congenital stationary night blindness (CSNB) revealed a novel homozygous splice site mutation in CACNA1F in the two girls transmitted from both the father and the mother. While in males the above clinical constellation is a frequent finding, this report, to the authorsâ knowledge, is the first demonstrating biallelic mutations at the CACNA1F locus in females.
Keywords: ddc:610